Beneficiaries perceptions on motivation to family planning intervention in a community of Karachi Pakistan - Chand, Zaheer; Bhamani, Shelina; Syed, Areeba; Abbas , Maliha; Karim, Zaibunissa; Sheikh, Lumaan (International Journal Of Community Medicine And Public Health, 2023)
Background: Pakistan is facing a great challenge in planning, implementing, and sustaining family planning and birth control policies. Considering this, one of the community health programs in the outskirts of a community health worked led family planning counselling. The purpose of this research study is to highlight perceptions of the beneficiaries regarding the benefits of the same. Methods: A qualitative descriptive study was undertaken for this investigation using a non-random sampling technique. The sample was chosen from the community population who were part of this intervention, with an inclusion criterion. The data was collected using in-depth interviews from 13 participants in total. Results: The key themes emerged across the interviews: Unfolding myths: Participants’ recognized that using family planning mediums does not mean that there is a medical deficiency outcome to it but a way to prevent large families, societal pressure: Participants shared the issues and cultural taboos attached to the family planning and how it is conceived in their societies, program support: participants shared that having a female lady health worker coming to the home brings in more access to the family planning and benefits: they found that effective and structured family planning is contributing to their enhanced personal life relations, economic gains and social comfort. Conclusions: A community health program model can be one of the outlets the government can collaborate to offer door to door provision, service quality and access to family planning to such communities in need.